The Impact of a Master’s Degree in Social Sciences: Career Life Course and Income - Qureshi, Saiqa Anne (Researchparks Publishing, 2023)
This chapter explores the impact of a Master’s Degree in Social Sciences on income and career life course. It considers the verifiable economic impact of gaining a masters degree, and then considers the impact on career. This includes initial recruitment, resilience to redundancy, ability to pivot, trajectory including speed of ascent and level of seniority. It also mitigates general concerns about the terminal master’s degree as a program.